2015
DOI: 10.1109/jlt.2014.2378031
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Joints Between Metal Surfaces and Metal-Coated Fibers for Application in High Temperature Optical Fiber Sensors

Abstract: In this study, an innovative method is presented for preparing optical fibers for application in fiber optic sensors operating in harsh environments. It is shown, how to attach a metalcoated fiber electrolytically to a metal sensing element, as well as an electroless method for depositing a nickel protective layer on optical fibers. Additionally, the results of the reliability tests of these methods are presented. It is also shown, that by depositing an additional nickel protective layer, it is possible to slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our previous work [15,16] showed that developed optical fiber with nickel protective layer (Ni is a diffusion barrier and additional protection) are resistant to the oxidation process, the method of protecting the fiber is robust and may find application in industrial fiber sensors. Scheme of an optical oxygen sensor located in the exhaust of a temperature ranging from 350°C to 700°C is shown on Fig.…”
Section: High Temperature Luminescence Oxygen Sensormentioning
confidence: 99%
“…Our previous work [15,16] showed that developed optical fiber with nickel protective layer (Ni is a diffusion barrier and additional protection) are resistant to the oxidation process, the method of protecting the fiber is robust and may find application in industrial fiber sensors. Scheme of an optical oxygen sensor located in the exhaust of a temperature ranging from 350°C to 700°C is shown on Fig.…”
Section: High Temperature Luminescence Oxygen Sensormentioning
confidence: 99%
“…Now, many optical methods and typical structures are used to research of temperature and stress fiber sensors, and the main methods include using Rayleigh scattering [2], Raman scattering [3], reflection [4], interference [5], evanescent field [6], and so on, and measuring optical signal intensity, phase, polarization state changes with the temperature or stress variation [7][8]. The mainly used optical structure has the Fabry-Perot (F-P) cavity [9], fiber grating [10], fiber grating array [11], and fiber ring resonator [12], and the applied fiber has a single-mode and multimode, photonic crystal fiber, microstructured fiber, and birefringent fiber. In above methods, the fiber Mach-Zehnder interference (MZI) has the advantages of simple structure, low cost, high sensitivity, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-optic temperature sensors have high precision, low cost, and distributed multipoints in temperature measurement, and they are not affected by electromagnetic interference. With optical fibers adopted with a silica inner core, high temperatures of 1000°C have been measured [12][13][14]. The first-order sapphire Bragg gratings were fabricated by Elsmann et al and the highest temperature at 1200°C [15].…”
Section: Introductionmentioning
confidence: 99%